(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Simultaneous translation demands exceptional linguistic and cognitive ability from interpreters, with speech compression standing out as a foundational skill essential for conveying messages efficiently within tight time constraints. This article explores the theoretical foundation of speech compression during simultaneous translation, examining the cognitive processes involved, the linguistic strategies employed, and the nuances that shape interpreters’ ability to compress speech effectively. By analyzing this theoretical framework, we aim to clarify the complexities of speech compression in simultaneous translation and its pivotal role in enabling seamless cross-linguistic communication.